High-throughput screening of drug libraries identifies a new synergistic drug combination for the treatment of retinoblastoma - Po-Jen Tseng; Irina L. Sinenko; Marc Chambon; Damiano Banfi; Santiago Zugbi; María Belén Cancela; Kseniya A. Glinkina; Gerardo Turcatti; Christina Stathopoulos; Paula Schaiquevich; Francis L. Munier; Paul J. Dyson (PLoS ONE, 2026)
Retinoblastoma (RB) management often involves the combination of chemotherapeutic agents (e.g., carboplatin and etoposide) and techniques (e.g., chemotherapy and thermotherapy). Chemoresistance and relapse, as well as systemic and ocular toxicities of current retinoblastoma chemotherapeutics necessitate the implementation of alternative drugs. Fewer resources and concern for pediatric cancer hinder drug discovery and development in an effective way. To overcome the obstacle, a drug repurposing strategy without intuition was adopted to identify promising drug candidates that are both cytotoxic and selective towards human RB Y79 cells in vitro and an orthotopic xenograft mice model in vivo . By using high-throughput screening, gemcitabine demonstrated high cytotoxicity in Y79 cells, also potentially synergizing with thermotherapy, with minimal impact on a human retinal pigment epithelial RPE-1 cells. Furthermore, the synergistic effect of gemcitabine with carboplatin is superior to the clinically used combination of etoposide with carboplatin. Efficacy studies in orthotopic xenografts showed significant eye survival advantages after intravitreal gemcitabine administration or the combination of intravitreal gemcitabine with systemic carboplatin compared to relevant controls. Importantly, the combination resulted in lower tumor invasion in the optic nerves of the xenografts. Since gemcitabine is an FDA-approved chemotherapeutic agent, already used to treat other pediatric cancers, it could be repurposed to RB treatment alone or in combination with carboplatin, and potentially combined with thermotherapy, providing the basis for an alternative and improved treatment option for RB patients.